Interação parasito-hospedeiro entre espécies de Procamallanus (Nematoda, camallanidae) e de Leporinus (Osteichthyes, Anostomidae), no Reservatório da UHE de Nova Ponte - EPDA Galheiro - CEMIG (Perdizes, mg) - Feltran, Rodrigo de Barros (2003)
Fresh water fish parasite have beem widely described in literature, and the nematodes are the most common helminths of this kind of infection. The damage caused in the físh are very changeable, depending on the present specie, the invader organism and the amount of the envolved worms. The present work had as objective to identify the nematodes faune that attacks Leporinus friderici (Bloch, 1794) and Leporinus obtusidens (Valenciennes, 1836) and appraise the aspects of the parasite-host aspects. The físh was collected in the Nova Ponte plant power reservoir on the EPDA of Galheiro (CEMIG), Perdizes - MG. During the period of april 2002 from january 2003, it was collected 50 specimes of the host especie, using stationary nets and stick with físh-hooks. Inside the laboratory the captured físh had its total weigth, standard length and total length measured. After that, their eviscerated and their abdominal cavity was examined. The helminths research proceed through the direct exam of the digestive tube, and the attached organs, air bladder, kidneys and urinary bladder, gonads, heart and abdominal muscle wall. The found helmints was fíxed in warm “AFA”, individualistic and keeped in bottles with 70% etanol with 5% of glicerin. For the identification of the nematodes they were clear with latic acid and keeped between slide and coverglass, been observed with the optical microscopy help, obtaining the morphometric characteristics, for the identity confírmation. In the observed físh, 45 specimens of L. friderici and 40 de L. obtusidens, was found parasited with at least one specie of the intestinal nematodes. The nematodes species founded was: Procamallanus (Spirocamallanus) inopinatus Travassos, Artigas & Pereira, 1928 and Procamallanus (Spirocamallanus) iheringi Travassos, Artigas & Pereira, 1928. In L. friderici, P. (S.) inopinatus presented dominance, with prevalence rate of 90% against 2% of P. (S.) iheringi (only one infected host). While in L. obtusidens, didn’t present meaninful differences between the two spécies de nematodes, P. (S.) inopinatus with 56% e P. (S.) iheringi with 48%. To L. obtusidens, there was a meaninful and positive correlation between the host’s weigth, standard length and total length with the nematodes infection intensity. The studied parasite presented inner standard of aggregation distribution. Comparing to the infection for P. (S.) inopinatus, the two host species, a higher levei of aggregation was observed, when it was in interspecifíc interaction with P. (S.) iheringi The monospecifíc infections was the most common kind of infection in both host species, L. friderici with 97.8% and L. obtusidens with 72.5% from the host.